IMPLEMENTASI MODEL PENDIDIKAN RESOLUSI KONFLIK MELALUI PENDIDIKAN KEWARGANEGARAAN SEKOLAH MENENGAH ATAS - Bunyamin, Maftuh (2004)
The research is intrigued by the reality that so many social conflicts in society and conflicts among high school students in Indonesia that can not be solved democratically and constructively. This reality encourages the need of the implementation of Conflict Resolution Teaching Model for high school students. The focus of the research problem focuses on "To what extent Conflict Resolution Teaching Model using Workshop Approach through High School Civic Education is effective in improving students' knowledge and attitudes on conflict resolution?" The research is generally aimed to find the effectiveness of the implementation of Conflict Resolution Teaching Model through High School Civic Education. The research uses research and development as a research approach by integrating qualitative and quantitative approaches. Experimental design by One-group pretest-posttest design is used in the phases of piloting and empirical model validation and it is supported by observation and interview. The research uses percentage analysis, t-test, and qualitative analysis as data analysis techniques. The research results reveal that the implementation of Conflict Resolution Teaching Model is significantly effective in improving knowledge and attitudes of high school students toward conflict resolution. Students have more knowledge and positive toward conflict resolution. The implementation of model is also able to enhance students' conflict resolution skills, and to improve the quality of civic education teaching learning process. It is recommended that Conflict Resolution Teaching Model should be widely implemented in Indonesia schools by integrating to the existing curriculum or subject matters, especially to civic education and social studies education, which use reflective inquiry and problem solving learning approaches. Support from education decision makers and the willingness and the competency of school educational staffs will be very advantageous in implementing Conflict Resolution Teaching thoroughly in Indonesia.